Duration of Meconium Passage in Term and Preterm Infants (Anwer Khan Modern Medical College Journal, 2013)
Delayed first passage of meconium and also prolongation of meconium passage creates great anxiety among parents. Some study showed that that first passage of meconium is delayed in preterm infants compared to term infants. The difference in duration of meconium passage in term and preterm infant has however never been assessed before. This cross sectional study was carried between July 2010 to December 2010 among 100 Newborn babies ranging from 28 to 42 weeks of gestation who were delivered in the Department of Obstetrics and Gynaecology or admitted in the Department of Neonatology of Dhaka Medical college Hospital were included in the study. Gestational age was determined from first day of last menstruation (when available) and also by using Expanded Ballard Scoring System. In case of any discrepancy of more than 2 weeks, the later was accepted. This study was carrying out to determine the time of first passage of meconium and duration of passage of meconium in term and preterm infants. Out of total 100 infants, 58 were male and 42 were female. The numbers of babies were 21, 28, 25 and 26 in group I, II, III and IV respectively. The mean age at which the babies passed first meconium were 23.5±3.5, 33.0±3.8, 25.7±4.2 and 17.3±4.6 hours in group I, II, III and IV respectively, which was